Distributed H∞ Control of AVs Interacting by Uncertain and Switching Topology in a Platoon - Feng Gao; Dongfang Dang; Qiuxia Hu; Yingdong He (Journal of Advanced Transportation)
To overcome the challenges arising from the weakness of wireless communication, this paper presents a distributed H∞ control method for multi-AVs connected by an uncertain and switching topology in a platoon. After compensating for the powertrain nonlinearities, we model the node dynamics as a linear uncertain system. By applying the eigenvalue decomposition and linear transformation, the platoon system is decomposed to multiple low order subsystems depending on the eigenvalues of the topological matrix. The sufficient condition ensuring the robust performance of the platoon is presented by using the invariant of signal amplitude of the linear transformation. Then a numerical method is provided to solve the state feedback controller by using the LMI scheme. Only the bounds of the topological eigenvalues are necessary for this new synthesis method and the designed controller can govern the platoon composed of disturbed nodes and interacting by uncertain even switching topologies in a satisfactory way. The effectiveness of this distributed H∞ control strategy is validated by comparative bench tests between nominal and disturbed conditions.